1974
DOI: 10.1002/jsfa.2740250211
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid composition of the main phospholipid fractions of the rumen and abomasum tissues of foetal and adult sheep

Abstract: The fatty acid composition has been determined on phosphatidyl choline, phosphatidyl ethanolamine and sphingomyelin fractions earlier isolated from the rumen and abomasum tissues of foetal and of adult Romney sheep.The major proportion of polyunsaturated fatty acids was found in the phosphatidyl ethanolamine (17 to 43 %) fraction and this was reduced in the phosphatidyl choline (7 to 25 %) and sphingomyelin (1 to 4 %) fractions. These features are in keeping with the results for mammalian tissues generally. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
2

Year Published

1976
1976
1989
1989

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
2
1
2
Order By: Relevance
“…Hornstein et al (1961) only identified arachidonic acid in the phospholipid fraction of beef and pork; however, in a later study by the same group (Hornstein et al, 1967) they reported some three or four PUFAS in the phospholipid fraction of beef muscle. This is in contrast to the analyses reported recently for sheep muscle by Body and Shorland (1974), where they observed a wide range of C20 and C22 PUFAS and some 7% of 2,3-methylene fatty acids that had escaped the attention of other investigators. Hornstein et al (1961) also noted that the phospholipids and the total lipids developed rancid odors much more quickly than the neutral lipids, which adds further support to our contention that phospholipids play a major role in development of WOF.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Hornstein et al (1961) only identified arachidonic acid in the phospholipid fraction of beef and pork; however, in a later study by the same group (Hornstein et al, 1967) they reported some three or four PUFAS in the phospholipid fraction of beef muscle. This is in contrast to the analyses reported recently for sheep muscle by Body and Shorland (1974), where they observed a wide range of C20 and C22 PUFAS and some 7% of 2,3-methylene fatty acids that had escaped the attention of other investigators. Hornstein et al (1961) also noted that the phospholipids and the total lipids developed rancid odors much more quickly than the neutral lipids, which adds further support to our contention that phospholipids play a major role in development of WOF.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, linolenic (18:3) acid oxidizes twice as fast as linoleic (18:2), and arachidonic acid (20:4) twice as fast as linolenic. This indicates that the triglycerides are much less susceptible to oxidation than the phospholipids, which in the case of phosphatidylethanolamine from lamb tissues collectively contained up to 20% of the total fatty acids as tetra-, penta-, and hexaenoic acids (Body and Shorland, 1974). Thus, the importance of triglycerides in development of WOF would appear to have a minor influence as compared to that of the phospholipids, which is in agreement with the results of the present investigation.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the mean triglyceride contents of the 1. dorsi tissues fell within the range of 0.63-1.01%, which is comparable to the mean of 0.67 % quoted by Wrenn et al (1973) for intramuscular tissue. The phospholipids (0.75-1.01%) in the 1. dorsi tissues were relatively constant and similar to results of other workers (Link et al, 1967; Body and Shorland, 1974). " Mean of four animals.…”
supporting
confidence: 90%
“…The phospholipid fatty acids (Table IV) ranged from 12:0 to 22:5 6 and included traces of unidentified fatty acids with ECN's approximating 13:0 and 19:0, respectively. The presence in the dietary fats of no more than traces of linolenic acid (18:3 3) precluded the occurrence of substantial levels of a>3 polyunsaturated fatty acids as found in pasture-fed ruminants (Body and Shorland, 1974); nevertheless, some 20:5 3 was detected in the phospholipids in the present work.…”
contrasting
confidence: 58%
“…Both PC and PE may play an important role in the development of rancid flavors in stored meat or meat products because of their high content of PUFA (Igene et al, 1981). Corliss and Dugan (1970), Tsai and Smith (1971), and Sharma et al (1982) reported mat PE was more rapidly oxidized than me other PL classes as it contained more highly unsaturated fatty acids (Hornstein et al, 1961;Keller and Kinsella, 1973;Body and Shorland, 1974). Changes in PE and PC may be indicative of the extent of lipid oxidation.…”
Section: Effect Of Storage Cooking and Treatments On The Compositionmentioning
confidence: 94%